2005
DOI: 10.1177/0170840605050872
|View full text |Cite
|
Sign up to set email alerts
|

The Recomposition of an Organizational Field: Health Care in Alberta

Abstract: In this paper we develop a theoretical model that helps to understand change in mature organizational fields by emphasizing the role of competing institutional logics as part of a radical change process. Our investigation into a large-scale, government-led health reform initiative in Alberta, Canada, is based upon a qualitative case study approach to understanding the process of field recomposition. This study focuses on the later portions of change in an organizational field — that is, rather than explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
429
1
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(460 citation statements)
references
References 32 publications
10
429
1
12
Order By: Relevance
“…What is significant is that despite the adoption of the commercial logic for the elite soccer, Alliance Club KIL maintained the original logic and values associated with participant sport, volunteerism, and community orientation. This is similar to the finding of Reay and Hinings (2005) of their study of the health care system in a province in Canada that even though the '"business planning model" emphasizing efficiency and effectiveness, and the "medical professional model" centered on the physicians' expertise continued to exist in the system and had considerable sway in matters affecting the system. In a similar manner, even though the commercial logic displaced the volunteer logic for elite soccer in KIL, the volunteer logic continued to exist and influence key decisions in KIL.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…What is significant is that despite the adoption of the commercial logic for the elite soccer, Alliance Club KIL maintained the original logic and values associated with participant sport, volunteerism, and community orientation. This is similar to the finding of Reay and Hinings (2005) of their study of the health care system in a province in Canada that even though the '"business planning model" emphasizing efficiency and effectiveness, and the "medical professional model" centered on the physicians' expertise continued to exist in the system and had considerable sway in matters affecting the system. In a similar manner, even though the commercial logic displaced the volunteer logic for elite soccer in KIL, the volunteer logic continued to exist and influence key decisions in KIL.…”
Section: Discussionsupporting
confidence: 74%
“…This research is expected to contribute to the sparse literature on the practical and theoretical implications of operating in pluralistic institutional environments (Kraatz & Block, 2008). Reay and Hinings's (2005) study of health care services in Alberta, Canada, showed radical changes involving competing institutional logics within an organizational field. Yet, while the structure of the field and the dominant logic changed, the earlier dominant logic of the medical profession was not entirely removed by the business-like health care.…”
mentioning
confidence: 99%
“…In other instances, interdiscursivity (Phillips et al 2004) enables institutional entrepreneurs to appropriate legitimacy and meaning from other discourses. These borrowed institutional logics and practices from other, occasionally vastly dissimilar, fields can be very powerful, for example when market logics are applied to settings where they had previously been absent (Oakes, Townley and Cooper 1998;Reay andHinings 2005, Colyvas, 2007). Regardless of whether institutional entrepreneurs borrow and leverage dominant discourses well established within the field, or discourses ostensibly unrelated to the practice they are trying to diffuse (Rao 1998), comparison and analogy are prevalent mechanisms in discursive strategies used by institutional entrepreneurs.…”
Section: The Emergence Of Institutions and The Role Of Analogiesmentioning
confidence: 99%
“…Reay and Hinings 2005;Townley 2002) existing logicsis relatively well-studied. However, the role of analogy in shaping institutional design has not been explored in depth.…”
mentioning
confidence: 99%
“…While this exercise helps to locate and bound different organisations, an organisational field is not necessarily a stable or persistent environment (Reay and Hinings, 2005). The field of healthcare over the past 50 years has undergone significant changes, both in terms of the material-resource environment and in the beliefs, rules and logics that legitimate practice.…”
Section: Organisational Fieldmentioning
confidence: 99%